2014
DOI: 10.1088/0004-637x/785/2/131
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Wavelength Emissions From the Millisecond Pulsar Binary PSR J1023+0038 During an Accretion Active State

Abstract: Recent observations strongly suggest that the millisecond pulsar binary PSR J1023+0038 has developed an accretion disk since 2013 June. We present a multi-wavelength analysis of PSR J1023+0038, which reveals that (1) its gammarays suddenly brightened within a few days in 2013 June/July and has remained at a high gamma-ray state for several months; (2) both UV and X-ray fluxes have increased by roughly an order of magnitude; and (3) the spectral energy distribution has changed significantly after the gamma-ray … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
126
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(134 citation statements)
references
References 32 publications
8
126
0
Order By: Relevance
“…The spectrum is dominated by a blue continuum and strong, double-peaked emission lines of H and He. The spectrum appears similar to other optical spectra of the PSR J1023+0038 binary presented in the literature, both during the active period in 2000/2001 (Bond et al 2002;Wang et al 2009) and 2013/2014 (Halpern et al 2013;Coti Zelati et al 2014;Takata et al 2014). The optical spectra confirm that the accretion disk was present shortly after the end of the 2013 November X-ray observation.…”
Section: Optical Spectroscopysupporting
confidence: 86%
See 2 more Smart Citations
“…The spectrum is dominated by a blue continuum and strong, double-peaked emission lines of H and He. The spectrum appears similar to other optical spectra of the PSR J1023+0038 binary presented in the literature, both during the active period in 2000/2001 (Bond et al 2002;Wang et al 2009) and 2013/2014 (Halpern et al 2013;Coti Zelati et al 2014;Takata et al 2014). The optical spectra confirm that the accretion disk was present shortly after the end of the 2013 November X-ray observation.…”
Section: Optical Spectroscopysupporting
confidence: 86%
“…Swift has been used to regularly monitor the long-term behavior of PSR J1023+0038 since 2013 October (Coti Zelati et al 2014;Patruno et al 2014;Takata et al 2014). It observed the binary on 2013 November 10-13 and 2014 June 11 coincident with the XMM-Newton exposures.…”
Section: Swift Xrtmentioning
confidence: 99%
See 1 more Smart Citation
“…The system has been the subject of extensive multi-wavelength campaigns after its change of state (Halpern et al 2013;Kong 2013;Linares et al 2014;Patruno et al 2014;Takata et al 2014;Tendulkar et al 2014;Coti Zelati et al 2014;Deller et al 2015;Archibald et al 2015;Bogdanov et al 2015;Shahbaz et al 2015). Radio band observations performed by Deller et al (2015), in particular, showed a rapidly variable and flat spectrum that persisted over six months.…”
Section: Psr J1023+0038mentioning
confidence: 99%
“…The interaction between the pulsar magnetosphere/wind and the accretion disc is very dynamic, switching between different spectral states in X rays, with and without orbital modulation [98], and producing radio continuum emission and sporadic flares in the optical, UV, and X-rays, suggestive of propellor modes [97]. The γ-ray flux quintupled when the radio pulses disappeared [69,100]. γ-ray emission before the state change was likely powered by the pulsar, yet with only marginal detection of ms pulses [101].…”
Section: Millisecond Pulsar Arachnologymentioning
confidence: 99%